Interfacial precipitation and clogging in straight capillaries - Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Science, 2016)
Clogging of straight capillaries during interfacial precipitation (of common salt from saturated salt solution and acetone) was studied for a range of conditions that result in different flow regimes. The particle formation and clogging was explored using the images obtained by tracking a moving slug in real time. The flow regimes varied along the capillary length due to continuous mass transfer of acetone to water resulting in elongation of continuous phase slugs. In the slug flow regime, the precipitated particles formed solid shells/hemi spherical caps at the rear of acetone slugs, which eventually get detached from the interface. In the wavy parallel flow regime, where the interface is not flat, salting out was almost instantaneous and it led to faster clogging of the channels. Smaller Ca, i.e. lower flow rates or the use of smaller capillary length or using continuous fluid of relatively higher viscosity or lower interfacial tension can help to avoid or delay clogging. Formation of cohesive shells at the rear of a slug delayed clogging in the capillaries by delaying settling of individual particles. Parallel flow regime with a flat interface delayed the clogging significantly due to poor mass transfer as well as higher superficial velocities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Clogging time; Flow regime; Interfacial precipitation; Micro-capillary; Porous shells; slug flow

Antisolvent based precipitation: batch, capillary flow reactor and impinging jet reactor - Pal, Sayan; Madane, Ketan; Kulkarni, Amol A. (Chemical Engineering Journal, 2019)
A method for continuous antisolvent precipitation of ammonium perchlorate (AP) using a confined impinging jet reactor (CIJR) is studied. The geometry of the CIJR was optimized to achieve excellent mixing with a significant reduction in the particle deposition on walls. Initially, the experimental conditions were optimized in a batch system and then in a continuous capillary reactor. Later those conditions extended for antisolvent precipitation of AP in an impinging jet reactor using water and n-butyl alcohol as a solvent and antisolvent, respectively for optimum performance. The performance was compared with the experiments in batch mode as well as and in a continuous capillary reactor. Over a range of inlet jet velocity that corresponded to 1792 < Re < 7193 for the saturated aqueous solution of AP and 1135 < Re < 4553 for the antisolvent butanol phase, 8.98-16.98 mu m Ammonium perchlorate particles were attained.
Keywords: Ammonium perchlorate; Antisolvent precipitation; CFD; continuous flow; Impinging jet reactor; microparticles

Hydrodynamics and selectivity engineering of a multipoint dosing flow reactor - Shukla, Chinmay A.; Pal, Sayan; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2019)
This paper reports the suitability of a multipoint injection continuous flow reactor for carrying out a sequential reaction, while taking into account the associated hydrodynamics of such systems. Pressure drop was measured for different fluid injection patterns, viz., equal fluid dosing, decreasing dosing, and increasing dosing flow rates from the first to the last inlet. Moreover, residence time distribution was also explored. The data were compared with a conventional single-point injection. The extent of dispersion was found to be higher in the decreasing dosing profile compared to equally distributed dosing. Taking into account of these features, the suitability of such a reactor system for competitive-consecutive homogeneous nitration reaction was evaluated. The analysis was done on the basis of the Damkohler number (Da) for mixing and reaction. The rate-controlling phenomena were used to simulate the performance of the reactor for a range of a number of inlets, the mole ratio of reactants, and relative values of Da. The observations indicate that the multipoint injection is not beneficial for mixing controlled reactions. However, for reactions in the transient regime (i.e., 0.001 < t(m)/t(R) < 1000), it gives higher selectivity of the desired product.

Antisolvent based ultrasound-assisted batch and continuous flow precipitation of metformin hydrochloride particles - Pal, Sayan; Nikam, Arun V.; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Small sized particles of the antidiabetic drug metformin hydrochloride (MET.HCl) were produced by antisolvent based precipitation using an ultrasound assisted inverted jet reactor (IJR). This novel approach was implemented as a small passive mixer in which intensified turbulent mixing of the solution and the antisolvent occurred under controlled conditions. The optimized conditions for antisolvent precipitation (ASP) were investigated by studying the effect of solute concentration, antisolvent to solvent ratio and antisolvent temperature in batch systems. The optimized batch precipitation conditions were successfully translated into continuous flow process for the ultrasound assisted inverted jet reactor. The ability of the proposed clogging free inverted jet reactor approach can provide a scaled up alternative pathway to micro and millifluidic devices for manufacturing of small sized API particles, such as, MET.HCl for the formulations and encapsulations on an industrial scale.
Keywords: Continuous antisolvent precipitation; Jet-reactor; Metformin; supersaturation; Ultrasound

Effect of wettability on hydrodynamics and mass transfer in small capillaries - Sampat, Chaitanya; Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2021)
The wettability of the reactor wall has a significant effect on the interfacial liquid?liquid mass transfer rates in segmented flow. This work quantitatively demonstrates the importance of choosing the right material of construction of flow reactors to achieve the desired mass transfer performance. Glass and PTFE capillaries of identical diameter were used to study the effect of hydrophilic and hydrophobic surfaces on the hydrodynamics and mass transfer of the system. It was observed that for the overall mass transfer coefficient (kLa) changed by two orders of magnitude depending on the wettability of the continuous phase. The observations indicated that it is essential to achieve complete wetting of the capillary walls by the continuous phase for significant mass transfer enhancement. The observations are discussed on the basis of film thickness and slip velocity at the wall as well as the slip velocity at liquid?liquid interface. Predictions of the mass transfer coefficient using a model based on the interfacial and fluid properties showed excellent match with the experiments thereby allowing us to explore the effects of wettability on the overall mass transfer coefficient in greater detail. ? 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Liquid?liquid slug flow; Mass transfer; Slip velocity; Wettability

Impingement dynamics of jets in a confined impinging jet reactor - Pal, Sayan; Madane, Ketan; Mane, Mayur; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2021)
The interaction of two impinging liquid jets in a confined impinging jet reactor (CUR) is explored. Multiphase flow simulations were performed using the volume of fluids (VOF) approach to investigate the impingement dynamics of liquid impinging jets, and single-phase CFD simulations have been performed to understand the turbulence and the mixing performance in the system. At identical inlet velocities, the liquid sheet formed on the impingement axis was found to move toward the liquid jet inlet of the lesser density fluid until reaching equilibrium. The formation and transient movement of liquid sheets are characterized for different jet velocities. An improved reactor geometry is proposed that reduces the wall effect on sheet formation and wall deposition on discharge points of jets. Upon breaking away from the impinging film, the two liquid phases are found to be intertwined in the form of ligaments and droplets after fragmentation of the sheet, providing a higher interfacial confirmed by performing high-throughput continuous antisolvent precipitation.

Settling and spreading behaviour of particle clusters in quiescent liquids in confined vessels - Pal, Sayan; Kulkarni, Amol A. (Particuology, 2023)
Here we report experiments on particle cluster settling at high Reynolds number in quiescent liquid contained in a vessel. The particles were observed to spread at the vessel bottom surface in a nearcircular annular shape after settling irrespective of the shape of the vessel cross-section and particle shape, size, and types. Effect of different parameters such as mass, type and aspect ratio of the particles, height, and viscosity of liquid was investigated on spreading behaviour. Formation of the hemispherical bottom cap of the cluster that bounces upon hitting the vessel bottom surface was found to be responsible for the final circular annular shape of the settled structure. Particle leakage from the cluster was seen in the form of a tail. In the liquid having viscosity beyond 100 cP, cluster breakage was observed that resulted in hindered settling and asymmetric shapes of finally settled particles. The observations are useful to understand the overall area over which settling and spreading of such clusters can be observed. (c) 2023 Published by Elsevier B.V. on behalf of Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.
Keywords: Particle cluster; Settling; spreading; Temporal evolution